مسح بالإيكو والأشعة البسيطة للأطفال دون سن المشي لمراجعي مشفى الأسد الجامعي في اللاذقية لدراسة حالة عسرة تصنع الورك التطورية خبرة مشفى الأسد الجامعي باللاذقية خلال العام الدراسي 2002 – 2003 - ناصر فيصل; يوسف صفوان; محمد فؤاد محمد (Latakia University Journal -Medical Sciences Series, 2019)
الهدف من هذه الدراسة هو الوصول إلى نسبة تقريبية عن مدى حدوث عسرة تصنع الورك التطورية DDH في مجتمعنا ، ومدى ارتباط الإصابة بعوامل الخطورة ، ولذلك تم تقسيم مرضى الدراسة إلى مجموعتين المجموعة الأولى: تضم المواليد الجدد في قسم التوليد وكان عددهم 244 طفلا" ، حيث أجري لهم ثلاثة فحوص هي مسح الوركين بالإيكو في فترة ما بعد الولادة وفي عمر الشهر ومسح بالأشعة البسيطة في عمر أربعة أشهر ونصف وقد وصلنا إلى النتائج التالية : - نسبة حدوثDDH في الفحص الأول 59.83 % وفي الفحص الثاني 11.42 % وفي الفحص الثالث 5.5 % المجموعة الثانية: تضم الأطفال المراجعين للمشفى والذين عمرهم بين أربعين يوما" وحتى سن المشي ، وحصلنا على النتائج التالية : - نسبة حدوث DDH 9.09 % 0 - حالات DDH المشخصة في كلتا المجموعتين كان لديها عوامل خطورة للإصابةب DDH0 the objective of this study is to reach an approximate proportion about the happening range of developmental dysplasia of the hip (DDH) in our society, and to know how the injury is related to the risk factors. Therefore, the patients of this study were divided into two groups: The first group: which includes the new born in the obstetrical department, the number was 244, this group has three examinations: ultrasound scanning for the rwo hips in the period after birth, ultrasound examination when their age is one month, and X-ray scanning when the age is 4-5 months. The result were as following: the happening ratio in the first examination was 59.83% in the second examination was 11.42% andin the last examination was 5.5%. The second group: which includes the children (age between 40 days and the walking age), whom are visiting the hospital to make a check up, the examination results of this group were as following: The happening ratio of DDH was 9.09%. All the diacritic cases of DDH in both groups were having risk factors for DDH injury.